Biomechanical characteristic on lower extremity with or without chronic ankle instability during double leg drop landing - Jeon, K.; Park, J. (Korean Journal of Sport Biomechanics, 2021)
Objective: The purpose of this study was to investigate differences of landing strategy between people with or without chronic ankle instability (CAI) during double-leg drop landing. Method: 34 male adults participated in this study (CAI = 16, Normal = 18). Participants performed double-leg drop landing task on a 30 cm height and 20 cm horizontal distance away from the force plate. Lower Extremities Kinetic and Kinematic data were obtained using 8 motion capture cameras and 2 force plates and loading rate was calculated. Independent samples t-test were used to identify differences between groups. Results: Compared with normal group, CAI group exhibits significantly less hip internal rotation angle (CAI = 1.52±8.12, Normal = 10.63±8.44, p = 0.003), greater knee valgus angle (CAI = -6.78±5.03, Normal = -12.38 ±6.78, p = 0.011), greater ankle eversion moment (CAI = 0.0001±0.02, Normal = -0.03±0.05, p = 0.043), greater loading Rate (CAI = 32.65±15.52, Normal = 18.43±10.87, p = 0.003) on their affected limb during maximum vertical Ground Reaction Force moment. Conclusion: Our results demonstrated that CAI group exhibits compensatory movement to avoid ankle inversion during double-leg drop landing compared with normal group. Further study about how changed kinetic and kinematic affect shock absorption ability and injury risk in participants with CAI is needed.